Significant Role of Medicinal Botanicals Hostile to Cancer - Asim, Iram; Tanveer, Muhammad Ikrama; Yasmeen, Humaira (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
In medical systems, medicinal plants have always held an important place. Plant phytochemicals with known biological activity, such as antiviral, antibacterial, and anticancer properties, are crucial in treatment. It has demonstrated little to no negative effects in recent years and is regarded as safe to use. The use of medicinal plants is essential for preventing illnesses, especially cancer, which is the second leading cause of death worldwide. It was discovered that scientists had been effective in finding anti-cancer compounds up to this point such as eugenol, allicin, catechins, curcumin ursolic acid, anethol, lycopene, resveratrol, 6-gingerol from ginger, tomato, garlic, turmeric, blueberries, milk thistle, cranberries, walnuts which can assist in blocking or activating cancer cell activation signalling pathways cycloxigenase, matrix metalloproteinases MMP, COX-2, topoisomerase enzyme, Bax, Bak proteins and accelerating enzymes (antioxidant potential) that protect the body. Cancer is now treated with a few plant-based products and their phytoconstituents. Even though the management and control of cancer progression have advanced significantly, there are still many gaps and untapped prospects. As a result, this review article emphasizes the value of medicinal plants in maintaining human health as well as lists the phytochemicals from medicinal plants that can be used to cure cancer.